Real-time Dose Calculation in Radiographic Examination - Sookpeng, Supawitoo (Journal of Health Science of Thailand, 2018)
The primary purpose of this research was to develop the equation for calculation of patient entrance skin exposure (ESE) from radiographic examinations. Two models (A and B) of general xray equipment of governmental hospitals in Phitsanulok, Sukhothai and Kumpang Phet provinces were included in this study. The exposure was measured by Ionization chamber RADCAL 10X5-6M according to AAPM No. 31 recommendation. The results reveal that the equation was developed in terms of the voltage, current and time that used in radiographic examination, source skin distance, source detector distance and age of x-ray machine. The equations for both model A and B can be used for calculation of patient entrance skin exposure (ESE) with the mean percentage errors of ± 0.908 and ± 2.169 respectively.